The Efficacy of Nitrite Therapy for the Treatment of Heart Failure: A Meta-Analysis of Randomized Controlled Trials - Zhou, Quan; Zhang, Qin; Xu, Huaqiang (The Heart surgery forum, 2022)
The efficacy of nitrite therapy for the treatment of heart failure remains controversial. We conducted a systematic review and meta-analysis to explore the impact of nitrite therapy on heart failure. We searched the PubMed, EMbase, Web of Science, EBSCO, and Cochrane Library databases through November 2019 for randomized controlled trials (RCTs) assessing the effect of nitrite therapy on heart failure. This meta-analysis was performed using the random-effect model. Three RCTs are included in the meta-analysis. Overall, compared with the control group for heart failure, nitrite therapy is associated with significantly reduced PCWP (Std. MD=-1.22; 95% CI=-1.81 to -0.63; P < 0.0001) and improved PAC (Std. MD=0.71; 95% CI=0.16 to 1.27; P = 0.01), but reveals no substantial influence on peak VO2 (Std. MD=-0.19; 95% CI=-0.49 to 0.11; P = 0.21), systolic BP (Std. MD=-3.98; 95% CI=-8.24 to 0.28; P = 0.07), mean BP (Std. MD=-1.53; 95% CI=-3.37 to 0.31; P = 0.10), or heart rate (Std. MD=0.40; 95% CI=-0.14 to 0.94; P = 0.15). Nitrite therapy may show some benefits to heart failure.